On a neural phonon model of EEG brain dynamics - Christopher Batterton; Simeon Ensing; Craig Shepherd; Mahonri Owen; Jemma König; Mitchell Head (Journal of Computational Neuroscience, 2026)
Neuronal oscillations are a ubiquitous feature of brain activity, indexing functions from sensory selection to memory formation. Yet a unified framework that (i) accommodates the nonlinear, noise-driven nature of cortical dynamics and (ii) explains standard empirical measures—power, spectral entropy, coherence, Phase-Locking Value (PLV), Phase-Amplitude Coupling (PAC), and envelope correlations—remains elusive. A natural candidate is the noisy Stuart–Landau (SL) oscillator, whose deterministic form models cortical rhythms as limit cycles, while additive noise induces stochastic phase and amplitude fluctuations. Prior work has shown that networks of SL oscillators can replicate burst statistics, multistability, and cross-frequency modulation in electroencephalography/magnetoencephalography (EEG/MEG). However, an analytical framework linking these models directly to observed connectivity metrics has been lacking. Here we derive such a framework by mapping the Fokker–Planck equation (FPE) of each SL oscillator to an imaginary-time Schrödinger operator via a classical similarity transform. A second-order expansion around the limit-cycle amplitude yields a quadratic Hamiltonian whose ladder operators describe quantised fluctuations—neural phonons—in oscillatory power. Bilinear coupling terms inherited from diffusion give rise to analytically diagonalisable bosonic interactions. This construction yields closed-form expressions for spectral observables and their dynamics, including Green-function-derived coherence and PLV, perturbative PAC, and a five-parameter “personality map” linking microscopic physics to macroscopic brain states. By unifying noisy limit-cycle theory with operator methods from statistical physics, we introduce a tractable, interpretable formalism for understanding neural coherence as the dynamics of quantised phonons.

Reconstructing human–animal interactions via multiproxy analysis of dog paleofeces from the medieval Central Balkans - Nemanja Marković; Freya Steinhagen; Elena Marinova; Samantha Brown; Susan M. Mentzer; Christopher E. Miller; Maria A. Spyrou; Víctor Roces; Ella Reiter; Dejan Bulić; Mirjana Roksandić; Piers D. Mitchell; et al. (Archaeological and Anthropological Sciences, 2026)

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Identifying and reporting dystocia in laboratory rodents - Paul Barrow; Prägati S. Coder; Rashin Ghaffari; Leah Zorrilla; Christopher J. Bowman; Curtis E. Grace; Jason Manton; Alan Hoberman; Narinder Barraclough; Isabelle Leconte; Nicola Powles-Glover; Connie Chen; et al. (Reproductive Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Associations between cognitive frailty and circulating cardiovascular biomarkers in a memory clinic cohort - Xin Tong Tan; Joyce R. Chong; Eddie J. Y. Chong; Ming Ann Sim; Jiangbo Cui; Siew Pang Chan; Oi Wah Liew; Boon Yeow Tan; Narayanaswamy Venketasubramanian; Arthur Mark Richards; Mitchell K. P. Lai; Christopher Li-Hsian Chen (GeroScience, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Retrospective evaluation of the use of non-human primates for fertility assessment of pharmaceuticals submitted for marketing approval in the EU - Puck Roos; Diann L. Blanset; Peter JK. van Meer; Shermaine Mitchell-Ryan; Peter T. Theunissen; Katie J. Turner; Ronald L. Wange; Christopher J. Bowman (Regulatory Toxicology and Pharmacology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Fault timing and depocentre development in the northern Perth Basin during the evolution of the East Gondwana rift - Christopher Watts; Chris Elders; Mitchell O’Mara; Nicholas E. Timms; Hugo K.H. Olierook (Gondwana Research, 2025)

Offset Between Surface Elevation Table- and Sediment Core-Derived Accretion Rates: Case Study from Piermont Marsh, New York - Clara Chang; Sarah Fernald; Timothy Kenna; Christopher Mitchell; Christina Pacella; Margie Turrin; Jonathan Nichols; Steven Chillrud; Dorothy Peteet (Estuaries and Coasts, 2025)

New approach methodologies for assessing developmental toxicity of pharmaceuticals: Case examples and future directions - Nicola Powles-Glover; Allen R. Kaczor; Steven Van Cruchten; Christopher J. Bowman; Kimberly C. Brannen; Claudia Demarta-Gatsi; Isabelle LeConte; Amer Jamalpoor; Fumito Mikashima; Shermaine Mitchell-Ryan; Dinesh Stanislaus; Peter Theunissen; et al. (Reproductive Toxicology, 2025)

Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Historical increases in plant density increased vegetative maize biomass while breeding increased reproductive biomass and allocation to ear over stem - Ezequiel Saenz; Alejo Ruiz; Cintia Sciarresi; Kyle King; Mitchell Baum; Antonella Ferela; Gerasimos J.N. Danalatos; Brenda Gambin; George Kalogeropoulos; August Thies; Raziel A. Ordóñez; Slobodan Trifunovic; et al. (Field Crops Research, 2025)

Functional Traits of the World's Late Quaternary Terrestrial Mammalian Predators - Eamonn I. F. Wooster; Erick J. Lundgren; Mairin Balisi; Rhys T. Lemoine; Christopher J. Sandom; Jens‐Christian Svenning; John Rowan; Chris J. Jolly; Grant D. Linley; Mitchell. A. Cowan; Nick Wright; Dylan Westaway; et al. (Global Ecology and Biogeography, 2024)
Motivation Terrestrial predators play key roles in cycling nutrients, as well as limiting prey populations, and shaping the behaviour of their prey. Prehistoric, historic and ongoing declines of the world's predators have reshaped terrestrial ecosystems and are a topic of conservation concern. However, the availability of ecologically relevant predator functional traits is limited, hampering efforts to understand macroecological changes in this ecologically important functional group. Here, we present CarniTraits , a comprehensive open‐access functional trait database of all late Quaternary (~130,000 ybp) terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Main Types of Variables Contained Mammalian terrestrial predator functional traits including body mass, diet, scavenging, locomotion, cooperative hunting, hunting habitat, hunting method, bone consumption, temporal activity patterns, brain mass and encephalisation quotient. Spatial Location and Grain Global. Time Period and Grain Late Quaternary (the last ~130,000 years). Major Taxa and Level of Measurement All late Quaternary terrestrial mammalian predators (149 species, ≥1 kg body mass, ≥50% vertebrate meat consumption). Software Format csv.

Expanded Combined Loading Injury Criterion for the Human Lumbar Spine Under Dynamic Compression - Maria Ortiz-Paparoni; Joost Op ‘t Eynde; Christopher Eckersley; Concetta Morino; Mitchell Abrams; Derek Pang; Jason Kait; Frank Pintar; Narayan Yoganandan; Jason Moore; David Barnes; Kathryn Loftis; et al. (Annals of Biomedical Engineering, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

Using DNA metabarcoding to characterize national scale diatom-environment relationships and to develop indicators in streams and rivers of the United States - Nathan J. Smucker; Erik M. Pilgrim; Christopher T. Nietch; Leslie Gains-Germain; Charlie Carpenter; John A. Darling; Lester L. Yuan; Richard M. Mitchell; Amina I. Pollard (Science of The Total Environment, 2024)

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Cover crop cultivars and species differ in root traits potentially impacting their selection for ecosystem services - Kong M. Wong; Marcus Griffiths; Amelia Moran; Andrea Johnston; Alexander E. Liu; Mitchell A. Sellers; Christopher N. Topp (Plant and Soil, 2024)
Background and aims Cover crops have the potential to aid in adapting agricultural systems to climate change impacts through their ecosystem services, such as preventing soil erosion, remediating soil structure, and storing carbon belowground. Though roots are integral to these processes, there is a lack of cover crop root trait data. This study aims to characterize rooting behavior of several commercially available cover crops and assess how differences in root system architecture potentially impact their selection for ecosystem services. Methods Twenty-two cover crop cultivars across the grass, legume, and brassica families were grown in O’Fallon, Missouri, USA. Canopy cover was monitored throughout the growing season. Shoot and root biomass samples were collected and analyzed. Results Cereal rye and winter triticale were the most winter hardy cultivars and provided the highest percent canopy cover. Cereal rye and winter triticale also generated the highest amount of shoot and root biomass among treatments but diverged in their root system architectures. Winter triticale forms coarser roots and exhibited deeper rooting, which may be better suited for carbon sequestration. Rapeseed and Siberian kale have favorable C:N ratios for nutrient recycling, but rapeseed may invest more into lateral root formation and have a higher potential to “catch” excess nutrients. Conclusion Selection of cover crops for ecosystem services should account for root system architecture and their suitability for these ecosystem services. Differences in root traits among cultivars within the same family highlight the potential to breed cover crop root system architecture to further enhance ecosystem service efficacy.

Interactions between management context and tree water use influence stormwater management potential of urban forests - Sarah Ponte; A. Christopher Oishi; Nancy F. Sonti; Dexter H. Locke; Tuana H. Phillips; Mitchell A. Pavao-Zuckerman (Urban Forestry & Urban Greening, 2024)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Where the leatherbacks roam: movement behavior analyses reveal novel foraging locations along the Northwest Atlantic shelf - Mitchell J. Rider; Larisa Avens; Heather L. Haas; Joshua M. Hatch; Samir H. Patel; Christopher R. Sasso (Frontiers in Marine Science, 2024)
Leatherback sea turtles ( Dermochelys coriacea ) migrate along the east coast of the United States, traversing the South and Mid-Atlantic Bights (SAB and MAB) while traveling to and from well-known northern foraging areas off Southern New England (SNE) and Nova Scotia. However, there is limited information on leatherback movement behavior in these regions. To identify leatherback movement patterns, we fit hidden Markov models (HMMs) to satellite transmitter data from 52 leatherbacks tagged between 2017 and 2022 off the coasts of Massachusetts and North Carolina to estimate locations of area restricted searching (ARS) and transient behaviors. Depth-temperature profiles were then paired to locations associated with ARS behavior to understand the vertical use of the water column. We observed leatherbacks displaying ARS behavior in SNE as expected, but also in the MAB and SAB. The HMM results indicated that leatherbacks were primarily foraging in SNE between Nantucket and Long Island Sound and depth-temperature plots from ARS behavior on Nantucket Shoals implied turtles foraging throughout the entire water column. In the MAB, ARS behavior was concentrated between Cape Hatteras, North Carolina, and the mouth of Delaware Bay during the summer. Turtles were closely associated with a well-defined thermocline, but still appeared to dive to deeper cooler waters, which may be a sign of thermoregulatory behavior. There was evidence of foraging in the SAB along the coast as well as along the continental shelf edge. The ARS behavior we documented within the MAB and SAB is the first published empirical evidence that both areas may be important foraging grounds. Our results lay a path for future research to understand how leatherbacks use these areas and the potential anthropogenic threats encountered while moving through these regions.

Integrating risk assessment methods for carbon storage: A case study for the quest carbon capture and storage facility - Christopher F. Brown; Greg Lackey; Nate Mitchell; Seunghwan Baek; Brandon Schwartz; Marcella Dean; Robert Dilmore; Hein Blanke; Simon O'Brien; Carrie Rowe (International Journal of Greenhouse Gas Control, 2023)

Magmatic ignitor kick-starts subduction initiation - Jianfeng Yang; Ross N. Mitchell; Christopher J. Spencer; Baolu Sun; Chang Zhang; Liang Zhao (Gondwana Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Articles You Might Have Missed - Christopher P. Mitchell; Elizabeth G. Shanahan (Journal of Medical Toxicology, 2023)

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Narrow root cone angle promotes deeper rooting, cooler canopy temperatures and higher grain yield in a rice (Oryza sativa L.) recombinant inbred line population grown under different water availabilities in aerobic production systems - Ricky Vinarao; Christopher Proud; Peter Snell; Shu Fukai; Jaquie Mitchell (Field Crops Research, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Good Practices for the Laboratory Performance Testing of Aqueous Oral Inhaled Products (OIPs): an Assessment from the International Pharmaceutical Aerosol Consortium on Regulation and Science (IPAC-RS) - Jolyon P. Mitchell; I. Carter; J. D. Christopher; M. Copley; W. H. Doub; A. Goodey; C. J. Gruenloh; B. B. Larson; S. Lyapustina; R. B. Patel; S. W. Stein; J. D. Suman (AAPS PharmSciTech, 2023)

Minimal adaptation of the molecular regulators of mitochondrial dynamics in response to unilateral limb immobilisation and retraining in middle-aged men - Chantal A. Pileggi; Christopher P. Hedges; Randall F. D’Souza; Brenan R. Durainayagam; Nina Zeng; Vandre C. Figueiredo; Anthony J. R. Hickey; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2023)

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Testing unified theories for ozone response in C 4 species - Shuai Li; Christopher A. Moller; Noah G. Mitchell; DoKyoung Lee; Erik J. Sacks; Elizabeth A. Ainsworth (Global Change Biology, 2022)
There is tremendous interspecific variability in O 3 sensitivity among C 3 species, but variation among C 4 species has been less clearly documented. It is also unclear whether stomatal conductance and leaf structure such as leaf mass per area (LMA) determine the variation in sensitivity to O 3 across species. In this study, we investigated leaf morphological, chemical, and photosynthetic responses of 22 genotypes of four C 4 bioenergy species (switchgrass, sorghum, maize, and miscanthus) to elevated O 3 in side‐by‐side field experiments using free‐air O 3 concentration enrichment (FACE). The C 4 species varied largely in leaf morphology, physiology, and nutrient composition. Elevated O 3 did not alter leaf morphology, nutrient content, stomatal conductance, chlorophyll fluorescence, and respiration in most genotypes but reduced net CO 2 assimilation in maize and photosynthetic capacity in sorghum and maize. Species with lower LMA and higher stomatal conductance tended to show greater losses in photosynthetic rate and capacity in elevated O 3 compared with species with higher LMA and lower stomatal conductance. Stomatal conductance was the strongest determinant of leaf photosynthetic rate and capacity. The response of both area‐ and mass‐based leaf photosynthetic rate and capacity to elevated O 3 were not affected by LMA directly but negatively influenced by LMA indirectly through stomatal conductance. These results demonstrate that there is significant variation in O 3 sensitivity among C 4 species with maize and sorghum showing greater sensitivity of photosynthesis to O 3 than switchgrass and miscanthus. Interspecific variation in O 3 sensitivity was determined by direct effects of stomatal conductance and indirect effects of LMA. This is the first study to provide a test of unifying theories explaining variation in O 3 sensitivity in C 4 bioenergy grasses. These findings advance understanding of O 3 tolerance in C 4 grasses and could aid in optimal placement of diverse C 4 bioenergy feedstock across a polluted landscape.

Perceptions of and barriers to cancer screening by the sexual and gender minority community: a glimpse into the health care disparity - Joseph Lombardo; Kevin Ko; Ayako Shimada; Nicolas Nelson; Christopher Wright; Jerry Chen; Alisha Maity; Marissa L. Ruggiero; Scott Richard; Dimitrios Papanagnou; Edith Mitchell; Amy Leader; et al. (Cancer Causes & Control, 2022)

Evaluating the Effects of a Deep-Water Marine Protected Area a Decade After Closure: A Multifaceted Approach Reveals Equivocal Benefits to Reef Fish Populations - Brendan J. Runde; Jeffrey A. Buckel; Paul J. Rudershausen; Warren A. Mitchell; Erik Ebert; Jie Cao; J. Christopher Taylor (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are increasingly used to rebuild fish populations. In 2009, eight MPAs were designated off the southeast United States with the goal of rebuilding populations of long-lived deep-water reef fishes. We tested whether reef fish within the largest of these MPAs, the Snowy Wreck Marine Protected Area (SWMPA), have increased in size and abundance relative to a nearby control area and compared to pre-closure. Hurdle models fitted through Bayesian inference on echosounder data collected in 2007–2009 and 2018–2020 yielded no evidence of an MPA effect. Comparisons of catch-per-unit-effort (CPUE) of all reef fishes yielded similar null results. However, CPUE of reef species with formal stock assessments increased 47% in the SWMPA and decreased 50% in the control area. We found significant increases in mean length of red porgy ( Pagrus pagrus ) inside the SWMPA but not in the control area. We also found community composition changes, including shifts away from groupers (Serranidae; Epinephelinae) and toward snappers (Lutjanidae) and tilefish (Malacanthidae) in both areas, though we did not detect an MPA effect with this analysis. Our equivocal results indicate that more time and stricter enforcement may be necessary before more biological effects of the SWMPA can be detected.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Molecular Dynamics Simulations and Experimental Results Provide Insight into Clinical Performance Differences between Sandimmune® and Neoral® Lipid-Based Formulations - Dallas B. Warren; Shadabul Haque; Mitchell P. McInerney; Karen M. Corbett; Endri Kastrati; Leigh Ford; Hywel D. Williams; Vincent Jannin; Hassan Benameur; Christopher J.H. Porter; David K. Chalmers; Colin W. Pouton (Pharmaceutical Research, 2021)

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Preclinical and Clinical Evidence for the Involvement of Sphingosine 1-Phosphate Signaling in the Pathophysiology of Vascular Cognitive Impairment - Xin Ying Chua; Leona T. Y. Ho; Ping Xiang; Wee Siong Chew; Brenda Wan Shing Lam; Christopher P. Chen; Wei-Yi Ong; Mitchell K. P. Lai; Deron R. Herr (NeuroMolecular Medicine, 2021)

Response to Letter to the Editor: Are five 60-min sessions of isothermic heat acclimation sufficient to elicit beneficial physiological adaptations? - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)

Calibration of a common shortwave multispectral camera system for quantitative agricultural applications - J. Burdette Barker; Wayne E. Woldt; Brian D. Wardlow; Christopher M. U. Neale; Mitchell S. Maguire; Bryan C. Leavitt; Derek M. Heeren (Precision Agriculture, 2020)

Adaptable Monitoring Package Development and Deployment: Lessons Learned for Integrated Instrumentation at Marine Energy Sites - Brian Polagye; James Joslin; Paul Murphy; Emma Cotter; Mitchell Scott; Paul Gibbs; Christopher Bassett; Andrew Stewart (Journal of Marine Science and Engineering, 2020)
Integrated instrumentation packages are an attractive option for environmental and ecological monitoring at marine energy sites, as they can support a range of sensors in a form factor compact enough for the operational constraints posed by energetic waves and currents. Here we present details of the architecture and performance for one such system—the Adaptable Monitoring Package—which supports active acoustic, passive acoustic, and optical sensing to quantify the physical environment and animal presence at marine energy sites. we describe cabled and autonomous deployments and contrast the relatively limited system capabilities in an autonomous operating mode with more expansive capabilities, including real-time data processing, afforded by shore power or in situ power harvesting from waves. Across these deployments, we describe sensor performance, outcomes for biological target classification algorithms using data from multibeam sonars and optical cameras, and the effectiveness of measures to limit biofouling and corrosion. On the basis of these experiences, we discuss the demonstrated requirements for integrated instrumentation, possible operational concepts for monitoring the environmental and ecological effects of marine energy converters using such systems, and the engineering trade-offs inherent in their development. Overall, we find that integrated instrumentation can provide powerful capabilities for observing rare events, managing the volume of data collected, and mitigating potential bias to marine animal behavior. These capabilities may be as relevant to the broader oceanographic community as they are to the emerging marine energy sector.

Using ancient DNA to quantify losses of genetic and species diversity in seabirds: a case study of Pterodroma petrels from a Pacific island - Anicee J. Lombal; Alexander T. Salis; Kieren J. Mitchell; Alan J. D. Tennyson; Lara D. Shepherd; Trevor H. Worthy; Eric J. Woehler; Jeremy J. Austin; Christopher P. Burridge (Biodiversity and Conservation, 2020)

Strain-specificity in the hydrogen sulphide signalling network following dietary restriction in recombinant inbred mice - Stephen E. Wilkie; Lorna Mulvey; William A. Sands; Diana E. Marcu; Roderick N. Carter; Nicholas M. Morton; Christopher Hine; James R. Mitchell; Colin Selman (GeroScience, 2020)
Modulation of the ageing process by dietary restriction (DR) across multiple taxa is well established. While the exact mechanism through which DR acts remains elusive, the gasotransmitter hydrogen sulphide (H 2 S) may play an important role. We employed a comparative-type approach using females from three ILSXISS recombinant inbred mouse strains previously reported to show differential lifespan responses following 40% DR. Following long-term (10 months) 40% DR, strain TejJ89—reported to show lifespan extension under DR—exhibited elevated hepatic H 2 S production relative to its strain-specific ad libitum (AL) control. Strain TejJ48 (no reported lifespan effect following 40% DR) exhibited significantly reduced hepatic H 2 S production, while H 2 S production was unaffected by DR in strain TejJ114 (shortened lifespan reported following 40% DR). These differences in H 2 S production were reflected in highly divergent gene and protein expression profiles of the major H 2 S production and disposal enzymes across strains. Increased hepatic H 2 S production in TejJ89 mice was associated with elevation of the mitochondrial H 2 S-producing enzyme 3-mercaptopyruvate sulfurtransferase (MPST). Our findings further support the potential role of H 2 S in DR-induced longevity and indicate the presence of genotypic-specificity in the production and disposal of hepatic H 2 S in response to 40% DR in mice.

Short-term isothermic heat acclimation elicits beneficial adaptations but medium-term elicits a more complete adaptation - Jodie N. Moss; Freya M. Bayne; Federico Castelli; Mitchell R. Naughton; Thomas C. Reeve; Steven J. Trangmar; Richard W. A. Mackenzie; Christopher J. Tyler (European Journal of Applied Physiology, 2020)
Purpose To investigate the effects of 60 min daily, short-term (STHA) and medium-term (MTHA) isothermic heat acclimation (HA) on the physiological and perceptual responses to exercise heat stress. Methods Sixteen, ultra-endurance runners (female = 3) visited the laboratory on 13 occasions. A 45 min sub-maximal (40% W max ) cycling heat stress test (HST) was completed in the heat (40 °C, 50% relative humidity) on the first (HST PRE ), seventh (HST STHA ) and thirteenth (HST MTHA ) visit. Participants completed 5 consecutive days of a 60 min isothermic HA protocol (target T re 38.5 °C) between HST PRE and HST STHA and 5 more between HST STHA and HST MTHA . Heart rate (HR), rectal ( T re ), skin ( T sk ) and mean body temperature ( T body ), perceived exertion (RPE), thermal comfort (TC) and sensation (TS) were recorded every 5 min. During HSTs, cortisol was measured pre and post and expired air was collected at 15, 30 and 45 min. Results At rest, T re and T body were lower in HST STHA and HST MTHA compared to HST PRE, but resting HR was not different between trials. Mean exercising T re , T sk , T body , and HR were lower in both HST STHA and HST MTHA compared to HST PRE . There were no differences between HST STHA and HST MTHA . Perceptual measurements were lowered by HA and further reduced during HST MTHA . Conclusion A 60 min a day isothermic STHA was successful at reducing physiological and perceptual strain experienced when exercising in the heat; however, MTHA offered a more complete adaptation.

Ingestion and Absorption of Eucalypt Monoterpenes in the Specialist Feeder, the Koala (Phascolarctos cinereus) - Caroline Marschner; Mark B. Krockenberger; Damien P. Higgins; Christopher Mitchell; Ben D. Moore (Journal of Chemical Ecology, 2019)

Juvenile and adult leaves of heteroblastic Eucalyptus globulus vary in xylem vulnerability - Christopher J. Lucani; Timothy J. Brodribb; Greg J. Jordan; Patrick J. Mitchell (Trees, 2019)

Determination of Passive Dry Powder Inhaler Aerodynamic Particle Size Distribution by Multi-Stage Cascade Impactor: International Pharmaceutical Aerosol Consortium on Regulation & Science (IPAC-RS) Recommendations to Support Both Product Quality Control and Clinical Programs - Jolyon P. Mitchell; Stephen W. Stein; William Doub; Adrian P. Goodey; J. David Christopher; Rajni B. Patel; Terrence P. Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2019)

Treading Water: Tools to Help US Coastal Communities Plan for Sea Level Rise Impacts - Emily A. Smith; William Sweet; Molly Mitchell; Ricardo Domingues; Christopher P. Weaver; Molly Baringer; Gustavo Goni; John Haines; J. Derek Loftis; John Boon; David Malmquist (Frontiers in Marine Science, 2019)

Deeply conserved susceptibility in a multi‐host, multi‐parasite system - Lisa N. Barrow; Sabrina M. McNew; Nora Mitchell; Spencer C. Galen; Holly L. Lutz; Heather Skeen; Thomas Valqui; Jason D. Weckstein; Christopher C. Witt (Ecology Letters, 2019)
Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection status, we applied Bayesian phylogenetic multilevel models that included a suite of environmental, spatial, temporal, life history and ecological predictors. We found evidence of deeply conserved susceptibility across the avian tree; host phylogeny explained substantial variation in infection status, and results were robust to phylogenetic uncertainty. Our study suggests that susceptibility is governed, in part, by conserved, latent aspects of anti‐parasite defence. This demonstrates the importance of deep phylogeny for understanding present‐day ecological interactions.

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Enhanced cutaneous wound healing in rats following topical delivery of insulin-loaded nanoparticles embedded in poly(vinyl alcohol)-borate hydrogels - Dalia H. Abdelkader; Murtaza M Tambuwala; Christopher A. Mitchell; Mohamed A. Osman; Sanaa A. El-Gizawy; Ahmed M. Faheem; Mohamed El-Tanani; Paul A. McCarron (Drug Delivery and Translational Research, 2018)

Aboveground carbon sequestration in dry temperate forests varies with climate not fire regime - Christopher E. Gordon; Eli R. Bendall; Mitchell G. Stares; Luke Collins; Ross A. Bradstock (Global Change Biology, 2018)
The storage of carbon in plant tissues and debris has been proposed as a method to offset anthropogenic increases in atmospheric [ CO 2 ]. Temperate forests represent significant above‐ground carbon ( AGC ) “sinks” because their relatively fast growth and slow decay rates optimise carbon assimilation. Fire is a common disturbance event in temperate forests globally that should strongly influence AGC because: discrete fires consume above‐ground biomass releasing carbon to the atmosphere, and the long‐term application of different fire‐regimes select for specific plant communities that sequester carbon at different rates. We investigated the latter process by quantifying AGC storage at 104 sites in the Sydney Basin Bioregion, Australia, relative to differences in components of the fire regime: frequency, severity and interfire interval. To predict the potential impacts of future climate change on fire/ AGC interactions, we stratified our field sites across gradients of mean annual temperature and precipitation and quantified within‐ and between‐factor interactions between the fire and climate variables. In agreement with previous studies, large trees were the primary AGC sink, accounting for ~70% of carbon at sites. Generalised additive models showed that mean annual temperature was the strongest predictor of AGC storage, with a 54% near‐linear decrease predicted across the 6.1°C temperature range experienced at sites. Mean annual precipitation, fire frequency, fire severity and interfire interval were consistently poor predictors of total above‐ground storage, although there were some significant relationships with component stocks. Our results show resilience of AGC to frequent and severe wildfire and suggest temperature mediated decreases in forest carbon storage under future climate change predictions.

The seafood supply chain from a fraudulent perspective - Michaela Fox; Mike Mitchell; Moira Dean; Christopher Elliott; Katrina Campbell (Food Security, 2018)

Interdisciplinary Oncology Education: a National Survey of Trainees and Program Directors in the United States - Adil S. Akthar; Christopher D. Hellekson; Sabha Ganai; Olwen M. Hahn; Ronald J. Maggiore; Ezra E. Cohen; Mitchell C. Posner; Steven J. Chmura; Andrew R. Howard; Daniel W. Golden (Journal of Cancer Education, 2018)

Microvascular ultrastructural changes precede cognitive impairment in the murine APPswe/PS1dE9 model of Alzheimer’s disease - Patricia Kelly; Paul Denver; Simon C. Satchell; Maximilian Ackermann; Moritz A. Konerding; Christopher A. Mitchell (Angiogenesis, 2017)

Discriminating Ability of Abbreviated Impactor Measurement Approach (AIM) to Detect Changes in Mass Median Aerodynamic Diameter (MMAD) of an Albuterol/Salbutamol pMDI Aerosol - J . David Christopher; Rajni B. Patel; Jolyon P. Mitchell; Terrence P. Tougas; Adrian P. Goodey; Jorge Quiroz; Patrik U. Andersson; Svetlana Lyapustina (AAPS PharmSciTech, 2017)

Estimating groundwater inflow and leakage outflow for an intermontane lake with a structurally complex geology: Georgetown Lake in Montana, USA - Glenn D. Shaw; Katie L. Mitchell; Christopher H. Gammons (Hydrogeology Journal, 2017)

Fracked ecology: Response of aquatic trophic structure and mercury biomagnification dynamics in the Marcellus Shale Formation - Christopher James Grant; Allison K. Lutz; Aaron D. Kulig; Mitchell R. Stanton (Ecotoxicology, 2016)

Ant biodiversity and its environmental predictors in the North Kimberley region of Australia’s seasonal tropics - Adam T. Cross; Cecilia Myers; Celia N. A. Mitchell; Sophie L. Cross; Christopher Jackson; Rowan Waina; Ladislav Mucina; Kingsley W. Dixon; Alan N. Andersen (Biodiversity and Conservation, 2016)

Altered relaxin family receptors RXFP1 and RXFP3 in the neocortex of depressed Alzheimer’s disease patients - Jasinda H. Lee; Shu Qing Koh; Simone Guadagna; Paul T. Francis; Margaret M. Esiri; Christopher P. Chen; Peter T.-H. Wong; Gavin S. Dawe; Mitchell K. P. Lai (Psychopharmacology, 2016)

Alternative approaches for addressing non-permanence in carbon projects: an application to afforestation and reforestation under the Clean Development Mechanism - Christopher S. Galik; Brian C. Murray; Stephen Mitchell; Phil Cottle (Mitigation and Adaptation Strategies for Global Change, 2016)

Synergy Between Intercellular Communication and Intracellular Ca2+ Handling in Arrhythmogenesis - Etienne Boileau; Christopher H. George; Dimitris Parthimos; Alice N. Mitchell; Sabina Aziz; Perumal Nithiarasu (Annals of Biomedical Engineering, 2015)

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Pathways toward whole community transformation: a case study on the role of school engagement and environmental education - Ingrid Kajzer Mitchell; Christopher Ling; Charles Krusekopf; Susan Kerr (Environment, Development and Sustainability, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Lack of in vitro–in vivo correlation for a UC781-releasing vaginal ring in macaques - Christopher McConville; James M. Smith; Clare F. McCoy; Priya Srinivasan; James Mitchell; Angela Holder; Ron A. Otten; Salvatore Butera; Gustavo F. Doncel; David R. Friend; R. Karl Malcolm (Drug Delivery and Translational Research, 2015)

Investigation of Dry Powder Inhaler (DPI) Resistance and Aerosol Dispersion Timing on Emitted Aerosol Aerodynamic Particle Sizing by Multistage Cascade Impactor when Sampled Volume Is Reduced from Compendial Value of 4 L - Hlack Mohammed; Jan Arp; Frank Chambers; Mark Copley; Volker Glaab; Mark Hammond; Derek Solomon; Kerry Bradford; Theresa Russell; Yvonne Sizer; Steven C. Nichols; Daryl L. Roberts; et al. (AAPS PharmSciTech, 2014)

Further observations of GPS satellite oscillator anomalies mimicking ionospheric phase scintillation - Christopher J. Benton; Cathryn N. Mitchell (GPS Solutions, 2014)

Observations on the crystal structures of lueshite - Roger H. Mitchell; Peter C. Burns; Kevin S. Knight; Christopher J. Howard; Anton R. Chakhmouradian (Physics and Chemistry of Minerals, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Rate of onset of inhibition of gut-wall and hepatic CYP3A by clarithromycin - Sara K. Quinney; Srikar R. Malireddy; Raj Vuppalanchi; Mitchell A. Hamman; Naga Chalasani; J. Christopher Gorski; Stephen D. Hall (European Journal of Clinical Pharmacology, 2013)

Cuticular hydrocarbons as a basis for chemosensory self‐referencing in crickets: a potentially universal mechanism facilitating polyandry in insects - Carie B. Weddle; Sandra Steiger; Christopher G. Hamaker; Geoffrey D. Ower; Christopher Mitchell; Scott K. Sakaluk; John Hunt (Ecology Letters, 2013)
Females of many species obtain benefits by mating polyandrously, and often prefer novel males over previous mates. However, how do females recognise previous mates, particularly in the face of cognitive constraints? Female crickets appear to have evolved a simple but effective solution: females imbue males with their own cuticular hydrocarbons ( CHC s) at mating and utilise chemosensory self‐referencing to recognise recent mates. Female CHC profiles exhibited significant additive genetic variation, demonstrating that genetically unique chemical cues are available to support chemosensory self‐referencing. CHC profiles of males became more similar to those of females after mating, indicating physical transfer of CHC s between individuals during copulation. Experimental perfuming of males with female CHC s resulted in a female aversion to males bearing chemical cues similar to their own. Chemosensory self‐referencing, therefore, could be a widespread mechanism by which females increase the diversity of their mating partners.

GPS satellite oscillator faults mimicking ionospheric phase scintillation - Christopher J. Benton; Cathryn N. Mitchell (GPS Solutions, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Cash, food, or vouchers? An application of the Market Information and Food Insecurity Response Analysis Framework in urban and rural Kenya - Hope Michelson; Erin C. Lentz; Richard Mulwa; Mitchell Morey; Laura Cramer; Megan McGlinchy; Christopher B. Barrett (Food Security, 2012)

Challenges with Developing In Vitro Dissolution Tests for Orally Inhaled Products (OIPs) - Trevor Riley; David Christopher; Jan Arp; Andrea Casazza; Agnes Colombani; Andrew Cooper; Monisha Dey; Janet Maas; Jolyon Mitchell; Maria Reiners; Nastaran Sigari; Terrence Tougas; et al. (AAPS PharmSciTech, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Fibrocyte-like cells recruited to the spleen support innate and adaptive immune responses to acute injury or infection - Tatiana Kisseleva; Maren von Köckritz-Blickwede; Donna Reichart; Shauna M. McGillvray; Gerhard Wingender; Mitchell Kronenberg; Christopher K. Glass; Victor Nizet; David A. Brenner (Journal of Molecular Medicine, 2011)

Product Lifecycle Approach to Cascade Impaction Measurements - Terrence P. Tougas; Dave Christopher; Jolyon Mitchell; Svetlana Lyapustina; Michiel Van Oort; Richard Bauer; Volker Glaab (AAPS PharmSciTech, 2011)

Differential involvement of hippocampal serotonin1A receptors and re-uptake sites in non-cognitive behaviors of Alzheimer’s disease - Mitchell K. P. Lai; Shirley W. Tsang; Margaret M. Esiri; Paul T. Francis; Peter T.-H. Wong; Christopher P. Chen (Psychopharmacology, 2011)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 2—Investigation of Bias in Extra-Fine Mass Fraction with AIM-HRT Impactor - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Effects of chronic and intermittent cocaine treatment on dominance, aggression, and oxytocin levels in post-lactational rats - Josephine M. Johns; Matthew S. McMurray; Paul W. Joyner; Thomas M. Jarrett; Sarah K. Williams; Elizabeth T. Cox; Mitchell A. Black; Christopher L. Middleton; Cheryl H. Walker (Psychopharmacology, 2010)

Relative Precision of Inhaler Aerodynamic Particle Size Distribution (APSD) Metrics by Full Resolution and Abbreviated Andersen Cascade Impactors (ACIs): Part 1 - Jolyon P. Mitchell; Mark W. Nagel; Cathy C. Doyle; Rubina S. Ali; Valentina I. Avvakoumova; J. David Christopher; Jorge Quiroz; Helen Strickland; Terrence Tougas; Svetlana Lyapustina (AAPS PharmSciTech, 2010)

Natural Variation of Flowering Time and Vernalization Responsiveness in Brachypodium distachyon - Christopher J. Schwartz; Mark R. Doyle; Antonio J. Manzaneda; Pedro J. Rey; Thomas Mitchell-Olds; Richard M. Amasino (BioEnergy Research, 2010)

Cascade Impactor (CI) Mensuration—An Assessment of the Accuracy and Precision of Commercially Available Optical Measurement Systems - Frank Chambers; Aziz Ali; Jolyon Mitchell; Christopher Shelton; Steve Nichols (AAPS PharmSciTech, 2010)

Improved Quality Control Metrics for Cascade Impaction Measurements of Orally Inhaled Drug Products (OIPs) - Terrence P. Tougas; David Christopher; Jolyon P. Mitchell; Helen Strickland; Bruce Wyka; Mike Van Oort; Svetlana Lyapustina (AAPS PharmSciTech, 2009)

Minimizing Variability of Cascade Impaction Measurements in Inhalers and Nebulizers - Matthew Bonam; David Christopher; David Cipolla; Brent Donovan; David Goodwin; Susan Holmes; Svetlana Lyapustina; Jolyon Mitchell; Steve Nichols; Gunilla Pettersson; Chris Quale; Nagaraja Rao; et al. (AAPS PharmSciTech, 2008)

Iron limitation across chlorophyll gradients in the southern Drake Passage: Phytoplankton responses to iron addition and photosynthetic indicators of iron stress - Brian M. Hopkinson; B. Greg Mitchell; Rick A. Reynolds; Haili Wang; Karen E. Selph; Christopher I. Measures; Christopher D. Hewes; Osmund Holm-Hansen; Katherine A. Barbeau (Limnology and Oceanography, 2007)
Processes influencing phytoplankton bloom development in the southern Drake Passage were studied using shipboard iron‐enrichment incubations conducted across a surface chlorophyll gradient near the Antarctic Peninsula, in a region of water mass mixing. Iron incubation assays showed that Antarctic Circumpolar Current (ACC) waters were severely iron limited, while shelf waters with high ambient iron concentrations (1–2 nmol L −1 ) were iron replete, demonstrating that mixing of the two water masses is a plausible mechanism for generation of the high phytoplankton biomass observed downstream of the Antarctic Peninsula. In downstream highchlorophyll mixed waters, phytoplankton growth rates were also iron limited, although responses to iron addition were generally more moderate as compared to ACC waters. Synthesizing results from all experiments, significant correlations were found between the initial measurements of Photosystem II (PSII) parameters ( F v :F m , σ PSII , and p ) and the subsequent responses of these waters to iron addition. These correlations indicate that PSII parameters can be used to assess the degree of iron stress experienced in these waters and likely in other regions where photoinhibition and nitrogen stress are not confounding factors.

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

Preparation and characterization of novel polymeric microcapsules for live cell encapsulation and therapy - Hongmei Chen; Wei Ouyang; Mitchell Jones; Terrence Metz; Christopher Martoni; Tasima Haque; Rebecca Cohen; Bisi Lawuyi; Satya Prakash (Cell Biochemistry and Biophysics, 2007)

Unique vascular phenotypes following over-expression of individual VEGFA isoforms from the developing lens - Christopher A. Mitchell; Catrin S. Rutland; Michael Walker; Muneeb Nasir; Alexander J. E. Foss; Christine Stewart; Holger Gerhardt; Moritz A. Konerding; Werner Risau; Hannes C. A. Drexler (Angiogenesis, 2006)

Contrasting stream water NO 3 − and Ca 2+ in two nearly adjacent catchments: the role of soil Ca and forest vegetation - SHEILA F. CHRISTOPHER; BLAIR D. PAGE; JOHN L. CAMPBELL; MYRON J. MITCHELL (Global Change Biology, 2006)
Two nearly adjacent subcatchments, located in the Adirondack Mountains of New York State, US, with similar atmospheric inputs of N (0.6 kmol ha −1 yr −1 ), but markedly different stream water solute concentrations, provided a unique opportunity to evaluate the mechanisms causing this variation. Subcatchment 14 (S14) had much greater stream water Ca 2+ and NO 3 − concentrations (851 and 73 μmol c L −1 , respectively) than Subcatchment 15 (S15) (427 and 26 μmol c L −1 , respectively). To elucidate factors affecting the variability in stream water concentrations, soil and forest floor samples from each subcatchment were analyzed for total elemental cations and extractable N species. Mineral soil samples were also analyzed for exchangeable cations. Tree species composition was characterized in each subcatchment and potential differences in land use history and hydrology were also assessed. Compared with S15, soils in S14 had significantly higher total elemental Ca 2+ in the forest floor (380 vs. 84 μmol g −1 ), Bs horizon (e.g. 1361 vs. 576 μmol g −1 ) and C horizon (1340 vs. 717 μmol g −1 ). Exchangeable Ca 2+ was also significantly higher in the mineral soil (64 μmol g −1 in S14 vs. 8 μmol g −1 in S15). Extractable NO 3 − was higher in S14 compared with S15 in both the forest floor (0.1 vs. 0.01 μmol g −1 ) and Bs horizon (0.2 vs. 0.07 μmol g −1 ) while extractable NH 4 + was higher in S14 vs. S15 in the forest floor (7 vs. 5 μmol g −1 ). The total basal area of ‘base‐rich indicator’ tree species (e.g. sugar maple, American basswood, eastern hophornbeam) was significantly greater in S14 compared with S15, which had species characteristic of sites with lower base concentrations (e.g. American beech and eastern white pine). The disparity in stream water Ca 2+ and NO 3 − , concentrations and fluxes between S14 and S15 were explained by differences in tree species composition and soil properties rather than differences in land use or hydrology. The marked difference in soil Ca 2+ concentrations in S14 vs. S15 corresponded to the higher stream water Ca 2+ and the larger contribution of base‐rich tree species to the overstory biomass in S14. Soil under such species is associated with higher net mineralization and nitrification and likely contributed to the higher NO 3 − concentrations in the drainage waters of S14 vs. S15. Studies investigating differences in spatial and temporal patterns of the effects of chronic N deposition on surface water chemistry need to account for changes in tree species composition and how vegetation composition is influenced by soil properties, as well as climatic and biotic changes.

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Impacts of changing climate and atmospheric deposition on N and S drainage losses from a forested watershed of the Adirondack Mountains, New York State - Ji‐Hyung Park; Myron J. Mitchell; Patrick J. McHale; Sheila F. Christopher; Tilden P. Meyers (Global Change Biology, 2003)
Biogeochemical responses to changing climate and atmospheric deposition were investigated using nitrogen (N) and sulfur (S) mass balances, including dry deposition and organic solutes in the Arbutus Lake watershed in the Adirondack Mountains, New York State. Long‐term monitoring of wet‐only precipitation (NADP/NTN, 1983–2001) and dry deposition (AIRMoN, 1990–2001) at sites adjacent to the watershed showed that concentrations of SO 4 2− in precipitation, SO 4 2− in particles,and SO 2 vapor all declined substantially ( P 4 + in precipitation, HNO 3 vapor, and particulate NO 3 − ), except for NO 3 − in precipitation, which showed a small decrease in the late 1990s. From 1983 to 2001, concentrations of SO 4 2− in the lake outlet significantly decreased (−2.1 μeq L −1 yr −1 , P 3 − and dissolved organic N (DON) concentrations showed no consistent temporal trends. With the inclusion of dry deposition and DON fluxes into the mass balance, the retained portion of atmospheric N inputs within the main subcatchment increased from 37% to 60%. Sulfur outputs greatly exceeded inputs even with the inclusion of dry S deposition, while organic S flux represented another source of S output, implying substantial internal S sources. A significant relationship between the annual mean concentrations of SO 4 2− in lake discharge and wet deposition over the last two decades ( r =0.64, P 4 2− concentrations, despite substantial internal S sources. By contrast, interannual variations in both NO 3 − concentrations and fluxes in lake discharge were significantly related to year‐to‐year changes in air temperature and runoff. Snowmelt responses to winter temperature fluctuations were crucial in explaining large portions of interannual variations in watershed NO 3 − export during the months preceding spring snowmelt (especially, January–March). Distinctive response patterns of monthly mean concentrations of NO 3 − and DON in the major lake inlet to seasonal changes in air temperature also suggested climatic regulation of seasonal patterns in watershed release of both N forms. The sensitive response of N drainage losses to climatic variability might explain the synchronous patterns of decadal variations in watershed NO 3 − export across the northeastern USA.

Molecular cloning and characterization of rainbow trout (Oncorhynchus mykiss) CCAAT/enhancer binding protein ? - Kazuhiro Fujiki; Lena Gerwick; Christopher J. Bayne; Leslie Mitchell; Julie Gauley; Niels Bols; Brian Dixon (Immunogenetics, 2003)

Integrated Environmental Assessment, Part I Estimating Emissions - H. Christopher Frey; Mitchell J. Small (Journal of Industrial Ecology, 2003)